Global phylogeography of the avian malaria pathogen Plasmodium relictum based on MSP1 allelic diversity. Issue 8 (22nd December 2014) - Hellgren, Olof; Atkinson, Carter T.; Bensch, Staffan; Albayrak, Tamer; Dimitrov, Dimitar; Ewen, John G.; Kim, Kyeong Soon; Lima, Marcos R.; Martin, Lynn; Palinauskas, Vaidas; Ricklefs, Robert; Sehgal, Ravinder N. M.; et al.
<x xml:space="preserve">Abstract</x> Knowing the genetic variation that occurs in pathogen populations and how it is distributed across geographical areas is essential to understand parasite epidemiology, local patterns of virulence, and evolution of host‐resistance. In addition, it is important to identify populations of pathogens that are evolutionarily independent and thus 'free' to adapt to hosts and environments. Here, we investigated genetic variation in the globally distributed, highly invasive avian malaria parasite Plasmodium relictum, which has several distinctive mitochondrial haplotyps (cyt b lineages, SGS1, GRW11 and GRW4). The phylogeography of P. relictum was accessed using the highly variable nuclear gene merozoite surface protein 1 (MSP1), a gene linked to the invasion biology of the parasite. We show that the lineage GRW4 is evolutionarily independent of GRW11 and SGS1 whereas GRW11 and SGS1 share MSP1 alleles and thus suggesting the presence of two distinct species (GRW4 versus SGS1 and GRW11). Further, there were significant differences in the global distribution of MSP1 alleles with differences between GRW4 alleles in the New and the Old World. For SGS1, a lineage formerly believed to have both tropical and temperate transmission, there were clear differences in MSP1 alleles transmitted in tropical Africa compared to the temperate regions of Europe and Asia. Further, we highlight the occurrence of multiple MSP1 alleles in GRW4 isolates from the Hawaiian Islands, where the parasite has contributed to declines and extinctions of endemic forest birds since it was introduced. This study stresses the importance of multiple independent loci for understanding patterns of transmission and evolutionary independence across avian malaria parasites.